Radiolabeling of Nanomaterials: Advantages and Challenges - Dai, Wanqin; Zhang, Junzhe; Wang, Yun; Jiao, Chunlei; Song, Zhuda; Ma, Yuhui; Ding, Yayun; Zhang, Zhiyong; He, Xiao (Frontiers in Toxicology, 2021)
Quantifying the distribution of nanomaterials in complex samples is of great significance to the toxicological research of nanomaterials as well as their clinical applications. Radiotracer technology is a powerful tool for biological and environmental tracing of nanomaterials because it has the advantages of high sensitivity and high reliability, and can be matched with some spatially resolved technologies for non-invasive, real-time detection. However, the radiolabeling operation of nanomaterials is relatively complicated, and fundamental studies on how to optimize the experimental procedures for the best radiolabeling of nanomaterials are still needed. This minireview looks back into the methods of radiolabeling of nanomaterials in previous work, and highlights the superiority of the “last-step” labeling strategy. It emphasizes the need to assess the ex vivo stability of chelator-assisted radiolabeling in the artificial lysosomal fluid and puts forward suggestions for further improvement.